Implementasi Rfid pada Perusahaan Penyewaan Mobil - I Gusti Made Karmawan (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Radio Frequency Identification (RFID) is an identification technology based on radio waves. At this time, we will describe the application of RFID technology in a rental car company. The study discusses about information about how to implement RFID within the enterprise, the role of RFID in the enterprise, how to use RFID, and everything else related to RFID in the enterprise. The  main purpose of writing this paper  is to make easy for reader finding information about general description of RFID and its application to a  car rental company. Furthermore,  methodology components are type and source of Data, data collection technique, hypotheses and data analysis technique. Finally, a conclusion is made that that RFID is an identification technology that is relatively new and feasible at the car rental company which is an alternative to barcodes that have been widely used. The presence of RFID also provides a very beneficial effect to the company, as has been displayed through charts of various aspects of the company in the results section.